Micropropagation of Leuce-poplar clones and its role in selection breeding - Balla, Ildikó; Keserű, Zsolt; Antal, Borbála; Rédei, Károly (Acta Agraria Debreceniensis, 2016)
Leuce-poplars (mostly white poplar and its natural hybrid grey poplar) are native tree species trough Hungary. They are covering more than 4.0 per cent of the Hungarian forested area (77 000 ha). The white (grey) poplars play a significant role in the forestation under sandy soil site conditions as well as they are of importance from nature conservation point of view as well.Long-term selection breeding work is going on at the National Agricultural Research and Innovation Centre Forest Research Institute (NARIC FRI), involving selection of fast-growing Leuce-poplar clones under dry site conditions.Micropropagation technology is relatively quickly spreading in forestry. In vitro multiplication of trees is applied mainly in fruit growing in Hungary, in case of forestry it is used mainly for selection breeding.This paper presents a short overview on the micropropagation trials with different Leuce-poplar clones and the early evaluation of the seedlings growing of the micropropagated clones/varieties.